ORGANIZATION AND PROFESSIONALISM COMMITMENT AGAINST AUDITOR PERFORMANCE - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research is intended to prove empi.J.ically: (1) The influence of organizational commitment on the auditor perfo1111ance; (2) The influence of professionalism on the auditor perfonnance; (3) The influence of organizational co1m11itment and professionalism on the auditor perfonnance. ID ln tllis research, to get the accurate result, tl1e ,,.,Titer uses associative approach. 'he population ill thi stud are all auditors workin in the ubli accounti.J.1g finn ill North Swnatra wllile sampling is rsatu ated sample. While tefllque in collecting data, it is used directly questionnaire to respondents, and the method of data analysis js multiple linear regression. 'fhe result shows that: (I) organizational commitment significantly influences the performance of the auditor, (2) professionalism also influences the auditor performance, (3) organizational commitment and professionalism also give a great effect on the auditor perfonnance.